2017
DOI: 10.1002/2017jc013065
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal changes in extreme sea levels along the coasts of the North Atlantic and the Gulf of Mexico

Abstract: Extreme sea levels along the densely monitored coasts of the North Atlantic Ocean and the Gulf of Mexico have been investigated using high‐frequency tide gauge measurements in the GESLA‐2 data set (http://www.gesla.org). Our results, based on nontidal residuals and skew surges in records since 1960, confirm that mean sea level (MSL) is a major, but not a unique, driver of extremes. Regionally coherent linear trends and correlations with large‐scale climate patterns are found in extreme events, even after the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
110
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 45 publications
15
110
1
Order By: Relevance
“…The introduction of seasonality in the extreme model allows to reproduce the behavior of NTR extreme values within the year. The evidence of the nonstationarity in sea level extreme events have been proved in previous studies at global (Menéndez & Woodworth, ), regional (Marcos & Woodworth, ), and local scales (Méndez et al, ; Menendez et al, ).…”
Section: Climate Variationsmentioning
confidence: 59%
See 2 more Smart Citations
“…The introduction of seasonality in the extreme model allows to reproduce the behavior of NTR extreme values within the year. The evidence of the nonstationarity in sea level extreme events have been proved in previous studies at global (Menéndez & Woodworth, ), regional (Marcos & Woodworth, ), and local scales (Méndez et al, ; Menendez et al, ).…”
Section: Climate Variationsmentioning
confidence: 59%
“…The results obtained along the coast using in situ measurements (Wahl & Chambers, 2015) agree with the previous ones, showing mainly a positive correlation along South and North Carolina coastline and the Gulf of Mexico. Several studies (Marcos & Woodworth, 2017;Menéndez & Woodworth, 2010) have already shown a correlation between La Niña phase and the occurrence of extreme events in the southern East Coast, mainly hit by the impact of TC's (see section 5.1).…”
Section: /2018jc014487mentioning
confidence: 96%
See 1 more Smart Citation
“…Studies of historical data have not found significant evidence in this region for larger storm tides due to the effect of climate change on storms (e.g., Marcos and Woodworth, 2017;Wahl and Chambers, 2016). Moreover, no quantitative evidence has been presented demonstrating that Hurricane Sandy was intensified or its storm tide was increased or made more likely by climate change (Lackmann, 2015;Mattingly et al, 2015).…”
Section: Current Coastal Flood Risksmentioning
confidence: 97%
“…To investigate such large-scale climate variability, climate indices (denoted CI) like North Atlantic Oscillation (NAO) or Atlantic Multidecadal Oscillation (AMO) have been used; see e.g. Menéndez and Woodworth (2010), Woodworth et al (2011), Talke et al (2014), Marcos et al (2015), Wahl andChambers (2015, 2016), Mawdsley and Haigh (2016), Marcos and Woodworth (2017), Wong et al (2018). Far from being theoretical, these research studies bring societal benefits.…”
Section: Introductionmentioning
confidence: 99%